PCV13 vaccine prevents pneumococcal biofilms without affecting Staphylococcus aureus population within the polymicrobial biofilm - Sempere, Julio; Yuste, José; Domenech, Mirian (Frontiers in Immunology, 2024)
In respiratory pathogens such as Streptococcus pneumoniae, biofilm formation is associated with the colonization of the nasopharynx and chronic respiratory infection. Previous data have shown that pneumococcal conjugate vaccines (PCVs) had an impact on S. pneumoniae colonization and a potential replacement by other respiratory pathogens such as Staphylococcus aureus. The objective of this work was to evaluate the evasion of the immune system by monospecific biofilms and by S. aureus- S. pneumoniae mixed biofilms. We performed opsonophagocytosis assays (OPA) using human HL-60 against previously disaggregated monospecific biofilms of MSSA, MRSA and S. aureus-S. pneumoniae mixed biofilms. We used pre-immune and post-immune serum from immunocompetent adult patients vaccinated with PCV13. Immune sera had a clear effect in reducing pneumococcal biofilms of serotypes 3, 14, 18C, 19F and 19A, whereas had no effect in non-PCV13 serotypes such as 8, 11A and 24F. Our study confirmed that serum from vaccinated patients with PCV13 did not have any effect in reducing S. aureus population in monospecific biofilms, regardless the methicillin resistance phenotype. Moreover, immunized sera from vaccinated patients with PCV13 did not have any effect in S. aureus population in the mixed biofilm, whereas significantly reduced the population of pneumococcal serotype 19A strain in the mixed biofilm which is of great interest because this serotype is included in PCV13, and it is associated with vaccine failures.